Understanding thermal alleviation in cold dwell fatigue in titanium alloys. (December 2018) - Zheng, Zebang; Stapleton, Adam; Fox, Kate; Dunne, Fionn P.E.
Abstract: Dwell fatigue facet nucleation has been investigated in isothermal rig disc spin tests and under anisothermal in-service engine conditions in titanium alloy IMI834 using α-HCP homogenised and faithful α-β lamellar microstructure crystal plasticity representations. The empirically observed facet nucleation and disc failure at low stress in the isothermal spin tests has been explained and originates from the material rate sensitivity giving rise to soft grain creep accumulation and hard grain basal stresses which increase with fatigue cycling until facet nucleation. The α-HCP homogenised model is not able to capture this observed behaviour at sensible applied stresses. In contrast to the isothermal spin tests, anisothermal in-service disc loading conditions generate soft grain slip accumulation predominantly in the first loading cycle after which no further load shedding nor soft grain creep accumulation is observed, such that the behaviour is stable, with no further increase in hard grain basal stress so that facet nucleation does not occur, as observed empirically. The thermal alleviation, which derives from in-service loading conditions and gives the insensitivity to dwell fatigue dependent on the temperature excursions, has been explained. A stress-temperature map for IMI834 alloy has been established to demarcate the ranges for which the propensity for dwell fatigue facet nucleation is high, threatening or low. Highlights: It is essential to include microstructural detail to capture local slip activities. Load shedding has been observed in isothermal rig disc spin test models. Creep accumulation does not occur under in-service engine conditions. Temperature plays a key role in cold dwell fatigue, in addition to stress. A dwell sensitivity map has been constructed for alloy IMI834.